The Implementation of Presentation Tasks in Teaching Public Speaking Skills at 6th grade Students of Al-Azhar 53 Islamic Elementary School Brebes - Arif Triyuono; Nur Riesta Fatimah Fitrihani (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Speaking is vital in English learning for expressing thoughts and communicating, but in elementary schools, especially public speaking, it is often overlooked and seen as too advanced. This research explores how the implementation of presentation tasks can help sixth-grade students’ public speaking skills at Al Azhar 53 Islamic Elementary School Brebes. This study used a qualitative descriptive method. The data were collected through observation, interviews, and documentation. The participants included one English teacher and 17 sixth-grade students. The presentation task was integrated into English learning through structured introduction, preparation, practice, and performance supported by Communicative Language Teaching (CLT) and Project-Based Learning (PjBL) approaches. The findings showed that the use of presentation tasks helped students become more confident, organised, and expressive in presenting their ideas. The students enjoyed the process, especially when utilising visual media such as PowerPoint and posters. The teacher also noted improvements in the students’ ability to communicate and collaborate. In conclusion, presentation tasks can serve not only as a speaking activity but also as a meaningful learning experience that nurtures confidence and life skills from an early age.